Influence of exothermic and modificating additives on the structure and characteristics of gray cast iron of cupola heat - V. M. Malov; O. A. Hitrova; I. I. Panchenko; O. I. Karabits (Литьë и металлургия)
In the real conditions of casting houses there is developed the technology of temperature raise of synthetic or half-synthetic hypoeutectic gray cast iron of cupola heat by 1525 C at insertion into bowl of 0,25% exothermal additive (EA), consisting of aluminium with iron oxide in proportion 1:3. At that there is guaranteed the production of the high quality castings with characteristics not below SCh20, solidity not higher of 229 HB, absence of spoilage on blow-holes and chills in thin cuts.